Association between Platelet-Lymphocyte Ratio and Proteinuria in T2DM Patient - Riyanti, Rini; Putri, Rona Andini; Sofiana, Kristianningrum Dian (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Diabetes Mellitus (DM) is a group of metabolic disorders characterized by hyperglycemia and glucose intolerance. Type 2 DM (T2DM) covers over 90% of DM cases. Diabetic nephropathy is a microvascular complication of DM. Proteinuria is as a marker of diabetic nephropathy in DM patients, which reflects disturbances of glomerular filtration and protein reabsorption. Platelet-to-Lymphocyte Ratio (PLR) is a new marker of inflammation and predictor of various medical conditions that is cheap and easy to access through a complete blood count. The pathophysiology of diabetic nephropathy has been reported to be related to chronic inflammation, hypercoagulation, and oxidative stress, which can affect the increase in the number of platelets and decrease in the number of lymphocytes. This study aimed to determine the correlation between PLR and proteinuria in T2DM patients. This cross-sectional study design used medical records data and involved patients presenting T2DM at dr. Soebandi Hospital, Jember from April 2021 to March 2023. The correlation between variables was analyzed using the Spearman correlation test (p <0.05). Based on the result with a subject of 98 T2DM patients, statistical analysis showed a significant correlation between PLR and proteinuria (p=0.000) with moderate strength of correlation (r=0.468). The average PLR value in T2DM patients with proteinuria was higher (255.41) than in T2DM patients without proteinuria (139.85).